The description of a novel Gloeothece species (Chroococcales, Cyanobacteria) from China, based on a polyphasic approach - Chen, Jiaxin; Li, Shuheng; Li, Renhui; Yu, Gongliang; Cai, Fangfang (Phytotaxa, 2024)
Cyanobacteria, with strong adaptability, occupied an important position on the earth all the time. In this study, the strain of coccoid cyanobacteria (CHAB 5847) was isolated and purified from Guizhou Province, China. The phylogenetic and taxonomic characteristics of CHAB 5847 were studied using polyphasic approach combining morphological, ecological and molecular data. Based on phylogenetic analysis of 16S rRNA gene sequence, the studied strain occupied a unique position, and clustered in Gloeothece clade. The 16S rRNA gene sequences of two clones of the studied strain shared 93.1%–98.1% similarity to other Gloeothece species, which supports well it to be a new member of Gloeothece genus. Furthermore, the unique pattern of D1-D1′, Box-B and V3 helix of the 16S–23S rRNA internal transcribed spacer (ITS) secondary structure revealed that the strain represented a novel species. These results support the establishment of a new species of Gloeothece genus with the name G. guizhouensis sp. nov.